2013
DOI: 10.1002/ggge.20254
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer‐scale characterization of microscopic pores in shale kerogen by image analysis and pore‐scale modeling

Abstract: [1] Nanometer-scale scanning electron microscopy was applied in visualizing the microscopic pores within shale kerogen. Geometrical information of all individual pores was extracted by image analysis. Image segmentation and separation showed that most of the intrakerogen pores are discrete and isolated from each other, having relatively spherical morphology. These isolated intrakerogen pores result in huge challenges in gas production, because they are not effectively connected to natural and hydraulic fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 34 publications
2
60
1
Order By: Relevance
“…The pore structures of shale are highly heterogeneous, with the pore size mainly ranging from nanometer to micrometer-sized [5,6]. Previous research has reported that nanometer-sized pores, which are predominantly associated with organic matter and clay minerals [6][7][8], could provide larger surface areas and higher adsorption energy for gas molecule adsorption [9][10][11][12], while micrometer-sized pores-which are generally associated with inorganic minerals [6]-are more likely to connect with induced fractures for gas flow and transport [13,14]. For gas desorption, once external conditions, such as temperature and pressure changes, for example, and artificial fractures disturb the equilibrium, the free gas molecules in fractures and macropore networks flow from high-pressure zones to low-pressure zones, and then gas that adsorbed onto the surface of organic matter and clay minerals starts to desorb, inducing a concentration gradient between the bulk particles and their surface.…”
Section: Introductionmentioning
confidence: 99%
“…The pore structures of shale are highly heterogeneous, with the pore size mainly ranging from nanometer to micrometer-sized [5,6]. Previous research has reported that nanometer-sized pores, which are predominantly associated with organic matter and clay minerals [6][7][8], could provide larger surface areas and higher adsorption energy for gas molecule adsorption [9][10][11][12], while micrometer-sized pores-which are generally associated with inorganic minerals [6]-are more likely to connect with induced fractures for gas flow and transport [13,14]. For gas desorption, once external conditions, such as temperature and pressure changes, for example, and artificial fractures disturb the equilibrium, the free gas molecules in fractures and macropore networks flow from high-pressure zones to low-pressure zones, and then gas that adsorbed onto the surface of organic matter and clay minerals starts to desorb, inducing a concentration gradient between the bulk particles and their surface.…”
Section: Introductionmentioning
confidence: 99%
“…Every pore cluster can be identified and labelled using the bwlabeln function in MATLAB ® . The pore clusters may be connected by hydraulic fractures (Chen et al 2013). An understanding of shale gas transport through pore clusters is thus critical to the evaluation of shale gas recovery.…”
Section: Data Descriptionmentioning
confidence: 99%
“…The 3D binary images are obtained by FIB-SEM imaging or reconstruction of a 2D SEM image (Chen et al 2013(Chen et al , 2015Ma et al 2014;Tahmasebi et al 2015), and the PNs can be extracted from the 3D images or artificially generated using constraints. Mehmani et al (2013) used local shrink and adjustment of the pore networks extracted from sandstone to approximate the micro-and nano-pore networks in shale and investigated the effect of the ratio of the nano-pores to the micro-pores on the apparent permeability using Javadpour (2009)'s flow flux formula.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The term shale play is used to describe a geographic area that contains an organicrich fine-grained sedimentary rock and exhibits low production rates. 4,5 Shale rocks are mainly composed of kerogen, quartz, clay, carbonates, and pyrite. Secondary components such as uranium, iron, vanadium, nickel, and molybdenum can be found in the shale matrix.…”
Section: Introductionmentioning
confidence: 99%